Knowledge frontiers: The concept of mechanobiology applied to strength training: Part two - Formicola, D. (EWF Scientific Magazine, 2019)
Knowing the variation of the shape and the direction of the forces of a muscle in contraction allows us to understand, therefore, its possibilities of intervention in the realization of sports movements and in its training modalities. Coaches, movement instructors, athletic and physical trainers, when creating training plans for their athletes, students, clients, tend to erroneously overlook the effects of muscle adaptation to physical exercise. A sports training programme must always begin with a careful biomechanical study of the execution technique of the athletic movement and must continue with a mechanobiological understanding of its practice. From a biomechanical point of view, in the different phases of athletic movements, the amplitudes to be covered with the joints, the accelerations to be achieved with the body segments and the inertia to be contrasted with the weight masses must be evaluated. From a mechanobiological point of view, on the other hand, it is essential to understand which exercises and operational strategies to adopt - and which to avoid - to obtain an anatomical remodeling of muscle tissues that effectively satisfies the biomechanical characteristics of the sports movement being perfected. This article aims to describe the changes in the mechanical and architectural properties of the muscles involved in exercises for the strength development, in line with the results of the most updated biomechanical and mechanobiological research applied to the sports training sector and physical preparation.